ANALISIS PENGARUH PENGANGGURAN DAN INFLASI TERHADAP KEMISKINAN DI SUMATERA UTARA TAHUN 2009-2017 - Sianturi, Vania Grace (Jurnal Manajemen dan Bisnis, 2020)
This study aims to provide empirical evidence of the influence of unemployment and inflation for poverty. The type of data used in this study is primary data with quantitative research method using multiple linear regression analysis technique and test hypotheses processed with Eviews 10. The result of data analysis showed that unemployment and inflation has a significant impact on the poverty. Seen from coefficient of determination that unemployment and inflation for poverty affect 63.95%, while the remaining 36.05% influenced by the others thay not included in this research.